MANAJEMEN REDAKSIONAL SURAT KABAR HARIAN UMUM HALUAN RIAU DALAM MENINGKATKAN KUALITAS PEMBERITAAN - Imam Maryanto; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The newspaper is one of the print media which has a long history compared to other media. It can be seen from the large number of newspaper publishing is still up and running. These circumstances affect the level of competition is certainly getting tougher in the printed newspaper itself, not to mention to Haluan Riau daily newspaper. In an effort to continue to survive in the competition, Haluan Riau demanded to produce an interesting and high quality news in order to satisfy the reader’s requirements. Editor, department who responsible for the news quality inseparable from the principles and elements of management, which became known as editor management. This research applies the method of qualitative descriptive approach undertaken in the daily newspaper Haluan Riau, Riau Press Building, 7th Tuanku Tambusai Street, Pekanbaru. Objects in this study is management of Haluan Riau’s editor, with research subjects include editorial director / deputy, editor, report coordinator, editorial secretary, and three journalists, as well as some of the readers who determined through purposive method. Data collection techniques used were observation, Interviews, and documentation.The results of this study is describes how the application of planning, organizing, actuating and controlling (POAC) in Haluan Riau as an effort to produce high quality news product. Planning implementation of Haluan Riau conducted in three forms editorship meetings, which includes news content planning meeting, personnel placement planning meetings, and projection meeting as well as an evaluation. As for organizing, Haluan Riau have determined the distribution of each personnel in accordance with the duties and responsibilities of each in accordance with the description of the specified work. Furthermore, regarding actuating in Haluan Riau’s editors carefully executed starting from the news coverage of the material, collecting, writing, editing news in order to avoid fatal factual errors, including the selection of designs and drawings / photographs. Forms of controlling carried out on Haluan Riau such as the projection meeting and pre mass production. The entire series of the process is a form of managerial committed to improving the quality of news editorial in Haluan Riau.Keywords : Newspaper, Editor, Management, POAC